80.1k views
5 votes
Please please please help meeeeee

Please please please help meeeeee-example-1

1 Answer

3 votes

Answer:

x = -4

Explanation:

Square both sides:


(√(-5-2x))^2 =(√(-1-x) )^2

The square root and the square will cancel to leave simply the argument within the square root:

-5 - 2x = -1 - x

Now simply isolate the variable x:

x = -5 + 1 = -4

Check to see if x = -4 will work:


√(-5-2*(-4)) =√(-1-(-4))


√(3) =√(3)

This works, so we know that x = -4 is a solution.

Hope this helps!

User TheWalkingCube
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.